P15.11 THE COURSE OF QOL AND NEUROCOGNITION IN NEWLY DIAGNOSED PATIENTS WITH GBM - Flechl, B. (Oxford University Press, 2014)
BACKGROUND: The importance of QOL and neurocognitive functions in patients with GBM is meanwhile beyond controversy. We followed newly diagnosed patients with GBM treated according to actual standard therapy during their course of disease by additionally evaluating their QOL and cognitive functions. METHODS: We included 42 consecutive patients with newly diagnosed GBM. To assess QOL we used the EORTC QLQ C30 and BN20 questionnaire. Neurocognition was measured with the NeuroCog FX. The evaluations were done 6 times every three months, beginning at the initiation of radiotherapy. RESULTS: 21/42 patients were able to do three assessments within 7 months. Afterwards, condition deterioration led to drop outs. The cognitive summary scale showed moderate impairment but remained stable. Patients with left-sided tumors showed significant lower scores in the subscale verbal fluency than patients with right-sided tumors during 4 months. The global health score of QOL decreased 20 points after the fifth evaluation whereas perceived fatigue symptoms were already increased one assessment before. Furthermore the patientś financial difficulties due to the disease increased strongly 7 months after diagnosis and were mentioned more frequently in younger patients and in patients with lower education levels. CONCLUSION: QOL and cognitive long-term assessments are feasible in patients with GBM before symptomatic progression occurs. Our study shows maintenance of QOL and cognitive summary scales before tumor progression and highlights subgroups according to tumor location and socioeconomic factors.